A Systems Theory of Organizational Conflict - Pondy, Louis R. (Academy of Management Journal, 1966)
Four ?subsystems? of activity within an organization are identified?informational, political, functional, and social. Conflict among the subunits of an organization may occur within any one of these subsystems. Informational conflict, in particular, is due to goal differences among interdependent subunits. But informational conflict affects and is affected by conflict occurring in the other three subsystems as well.